Staff Engagement is Key to Optimization. Issue 3 (1st March 2018) - Martin, Barb; Linder, Kevin
Abstract : Optimization is a team effort, requiring buy‐in and commitment from staff at all levels of an organization. Water and wastewater utilities are most effective in their optimization efforts when employees are provided the opportunity to collaborate, share ideas, and be empowered to achieve excellence.